2014
DOI: 10.1590/s1516-35982014000400006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phenolic compounds in propolis on digestive and ruminal parameters in dairy cows

Abstract: -Four rumen-cannulated primiparous lactating cows were studied in a 4 × 4 Latin square design experiment to evaluate the effects of propolis-based products (PBP) with different concentrations of propolis and alcohol levels on total digestibility, (TD), ruminal digestibility (RD), intestinal digestibility (ID), pH, ruminal ammonia-nitrogen production (NH 3 -N), rumen microbial synthesis, and blood parameters. The feed consisted of 591.9 g/kg corn silage and 408.1 g/kg concentrate (dry matter [DM] basis), and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
1
22
1
Order By: Relevance
“…The average ruminal pH was not affected (p > 0.05) by treatments applied, unlike the average concentration of N-NH 3 (p < 0.05, Table 1) (AGUIAR et al, 2014). Means followed by the same letter, into the row, do not differ at 5% of significance, according to the test of Tukey.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…The average ruminal pH was not affected (p > 0.05) by treatments applied, unlike the average concentration of N-NH 3 (p < 0.05, Table 1) (AGUIAR et al, 2014). Means followed by the same letter, into the row, do not differ at 5% of significance, according to the test of Tukey.…”
Section: Resultsmentioning
confidence: 85%
“…SE = Standard error. Source: Aguiar et al (2014). Aguiar et al (2014), on evaluating rumen pH as a function of time after feeding, found quadratic behavior (pH = 6.86944 -0.42107h + 0.042898h 2 ; R 2 = 73.6%) and estimated a minimum pH value of 5.83 at 4 h 54 min after feeding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations